Intracranial Pressure as an Objective Biomarker of Decompression Adequacy in Large Territory Infarction: A Multicenter Observational Study - Lim, Jia Xu; Liu, Sherry Jiani; Cheong, Tien Meng; Saffari, Seyed Ehsan; Han, Julian Xinguang; Chen, Min Wei (Frontiers in Surgery, 2022)
Background Decompressive craniectomy (DC) improves the survival and functional outcomes in patients with malignant cerebral infarction. Currently, there are no objective intraoperative markers that indicates adequate decompression. We hypothesise that closure intracranial pressure (ICP) correlates with postoperative outcomes. Methods This is a multicentre retrospective review of all 75 DCs performed for malignant cerebral infarction. The patients were divided into inadequate ICP (iICP) and good ICP (gICP) groups based on a suitable ICP threshold determined with tiered receiver operating characteristic and association analysis. Multivariable logistic regression was performed for various postoperative outcomes. Results An ICP threshold of 7mmHg was determined, with 36 patients (48.0%) and 39 patients (52.0%) in the iICP and gICP group, respectively. After adjustment, postoperative osmotherapy usage was more likely in the iICP group (OR 6.32, p = 0.003), and when given, was given for a longer median duration (iICP, 4 days; gICP, 1 day, p = 0.003). There was no difference in complications amongst both groups. When an ICP threshold of 11 mmHg was applied, there was significant difference in the duration on ventilator (ICP ≥11 mmHg, 3 – 9 days, ICP <11 mmHg, 3 – 5 days, p = 0.023). Conclusion Surgical decompression works complementarily with postoperative medical therapy to manage progressive cerebral edema in malignant cerebral infarctions. This is a proof-of-concept study which showed that closure ICP, a novel objective intraoperative biomarker, is able to guide the adequacy of DC in this condition. Various surgical manoeuvres can be performed to ensure that this surgical aim is accomplished.